2009
DOI: 10.1152/ajpregu.90899.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of coronary endothelial cell ETB receptor function after short-term inhalation exposure to whole diesel emissions

Abstract: Air pollutant levels positively correlate with increases in both acute and chronic cardiovascular disease. The pollutant diesel exhaust (DE) increases endothelin (ET) levels, suggesting that this peptide may contribute to DE-induced cardiovascular disease. We hypothesized that acute exposure to DE also enhances ET-1-mediated coronary artery constrictor sensitivity. Constrictor responses to KCl, U-46619, and ET-1 were recorded by videomicroscopy in pressurized intraseptal coronary arteries from rats exposed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 49 publications
5
51
1
Order By: Relevance
“…In separate experiments, diesel exhaust exposure to rats for 5 hours augmented ET-induced vasoconstriction, potentially via a blunting of ET-B-induced nitric oxide release. 365 The findings suggest that exposure to a fresh mixture of PM, gases, and vapors may play a role in rapidly triggering atherosclerotic plaque vulnerability via ROS and ET-dependent upregulation of MMP levels.…”
Section: Vascular Dysfunction and Atherosclerosismentioning
confidence: 91%
“…In separate experiments, diesel exhaust exposure to rats for 5 hours augmented ET-induced vasoconstriction, potentially via a blunting of ET-B-induced nitric oxide release. 365 The findings suggest that exposure to a fresh mixture of PM, gases, and vapors may play a role in rapidly triggering atherosclerotic plaque vulnerability via ROS and ET-dependent upregulation of MMP levels.…”
Section: Vascular Dysfunction and Atherosclerosismentioning
confidence: 91%
“…72 Inhaled particles might also interact with nociceptive or noradrenergic receptors to stimulate the sympathetic nervous system, raising circulating levels of vasoconstrictors, elevating blood pressure, and decreasing blood flow to the heart. 114 Neurogenic inflammation and the release of vasoactive mediators such as angiotensin II and en dothelin-1 can subsequently induce the expression of adhesion molecules, cytokines, and profibrotic mediators, and generate reactive oxygen species (ROS). 115 These effects can induce systemic inflammation, trigger plaque disruption and occlusion, or precipitate ischaemia-associated arrhythmia and myocardial damage.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 99%
“…In both studies, they were able to produce acute pulmonary changes and increases in blood fibrinogen with both concentrated ambient particles (CAPs) and concentrated DEP, but it took far higher concentrations of DEP than CAPs to do so. Others (USEPA, 2002;Hesterberg et al, 2005;Mills et al, 2005Mills et al, , 2007Li et al, 2007;Spira-Cohen et al, 2008;Cherng et al, 2009;Quan et al, 2010) have shown associations between human exposure to DEP and oxidative stress, proinflammatory cytokines, asthma aggravation, atherosclerotic disease, and a large number of other important health end points. In order words, exposure to DEP is widely understood to have significant effects on human health.…”
Section: Introductionmentioning
confidence: 99%